Preface to the special issue on quantitative information flow. (10th November 2014) - ANDRÉS, MIGUEL E.; PALAMIDESSI, CATUSCIA; SMITH, GEOFFREY
Abstract : A long-standing and fundamental issue in computer security is to control the flow of information, whether to prevent confidential information from being leaked, or to prevent trusted information from being tainted . While there have been many efforts aimed at preventing improper flows completely (see for example, the survey by Sabelfeld and Myers (2003)), it has long been recognized that perfection is often impossible in practice. A basic example is a login program – whenever it rejects an incorrect password, it unavoidably reveals that the secret password differs from the one that was entered. More subtly, systems may be vulnerable to side channel attacks, because observable characteristics like running time and power consumption may depend, at least partially, on sensitive information.